Ionic Liquid Functionalized Cu2O nanoparticles - Shukla M.; Pal S.; Sinha I. (My University, 2025)
The present study is on the photocatalytic activities of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid (IL) Cu2O nanoparticles. The morphological and structural characteristics of these NPs were studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HR-TEM). Copper (I) oxide (Cu2O) nanoparticles without stabilization were also prepared and investigated for comparison. The photocatalytic activities of the prepared nanoparticles were evaluated for methyl orange (MO) degradation under visible light. The IL functionalized Cu2O nanoparticles exhibited considerably enhanced photocatalytic activity. Density functional theory (DFT) calculations revealed the ground state electronic structure of the core-shell nanocluster. Electrostatic potential (ESP) charge showed a strong interaction between the Cu2O cluster and bmimBF4 IL. Density of State (DOS) calculation shows that the HOMO-LUMO gap of the Cu2O cluster-IL composite is significantly lesser than that of the Cu2O alone. © 2022 Elsevier B.V.